Peran Sikap sebagai Mediator dalam Adopsi Layanan Buy Now Pay Later dalam E-commerce Indonesia - Purwianti, Lily; Lady, Lady; Javita, Javita (Journal of Business and Economics Research (JBE), 2025)
This study aims to analyze the factors influencing the usage behavior of Buy Now Pay Later (BNPL) services among e-commerce users in Indonesia using the Unified Theory of Acceptance and Use of Technology (UTAUT) model. Four independent variables, performance expectancy, effort expectancy, social influence, and facilitating conditions, were examined, with attitude as a mediating variable. Data were collected from 340 respondents from Generations X, Y, and Z who had previously used BNPL services through an online questionnaire and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with 5,000 bootstrapping replications. The results indicate that performance expectancy has the strongest influence on user attitude (β = 0.363), while social influence has the weakest (β = 0.137). Attitude was found to be a crucial mediator linking external factors to BNPL usage. These findings provide theoretical contributions to the literature on financial technology adoption and practical implications for BNPL providers in designing communication strategies, financial literacy education, and supportive infrastructure to ensure more responsible and sustainable BNPL usage.